2009
DOI: 10.1007/s10750-009-0004-6
|View full text |Cite
|
Sign up to set email alerts
|

Mitochondrial DNA diversity and relationships of endemic charrs of the genus Salvelinus from Lake Kronotskoye (Kamchatka Peninsula)

Abstract: Lake Kronotskoye (the Kronotsky Biosphere State Reserve, south-eastern Kamchatka Peninsula) contains three closely related resident morphotypes charrs, which are considered to be either independent species (white charr Salvelinus albus, longhead charr Salvelinus kronocius, Schmidt's charr Salvelinus schmidti) or a united lacustrine-riverine charrs, represented by several phenotypes. Salvelinus malma malma is isolated from the lake charr populations by an upstream migration barrier in the Kronotskaya River, whi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
15
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(16 citation statements)
references
References 40 publications
(40 reference statements)
1
15
0
Order By: Relevance
“…Atlantic salmon Salmo salar was used as outgroup. The detailed laboratory protocol of mtDNA analysis was described earlier [11][12][13]. In accordance with the objectives of the study, different sets of 20 restriction endonucleases (MBI Fermentas, Lithuania; SibEnzyme, Russia) were used, including AsuI, AvaI, AvaII, BstNI, BstUI, DdeI, EcoRV, HhaI, HinfI, MboI, MboII, MspI, RsaI, StyI, BsuRI, VspI, BclI, SspI, Bme1390I, and TaqI.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Atlantic salmon Salmo salar was used as outgroup. The detailed laboratory protocol of mtDNA analysis was described earlier [11][12][13]. In accordance with the objectives of the study, different sets of 20 restriction endonucleases (MBI Fermentas, Lithuania; SibEnzyme, Russia) were used, including AsuI, AvaI, AvaII, BstNI, BstUI, DdeI, EcoRV, HhaI, HinfI, MboI, MboII, MspI, RsaI, StyI, BsuRI, VspI, BclI, SspI, Bme1390I, and TaqI.…”
Section: Methodsmentioning
confidence: 99%
“…Recent genealogical analysis of mtDNA haplotypes showed that the observed pattern most likely was the consequence of a complex combination of several factors in the back ground of ancestral polymorphism preservation [12,13]. However, at the present stage, it is impossible to see the difference between the influence of incomplete lineage segregation and historical introgression, as well as to estimate the gene flow in the young taxa pre serving ancestral polymorphism [36].…”
Section: S Confluentusmentioning
confidence: 97%
See 1 more Smart Citation
“…). The MNKR sample contains material collected near the river head (2003) and downstream (2004) (Oleinik and Skurikhina ). Two isolated populations (MNHL, MNKK) were represented by the landlocked ecological form of charrs.…”
Section: Methodsmentioning
confidence: 99%
“…The genus Salvelinus (commonly referred to as char) contains six widely recognized species: Bull Trout Salvelinus confluentus, Brook Trout S. fontinalis, Lake Trout S. namaycush, Dolly Varden S. malma, Arctic Char S. alpinus, and Whitespotted Char S. leucomaenis. The existence of additional Salvelinus species and subspecies has also been recognized or suggested (Dunham et al 2008;Oleinik and Skurikhina 2010). The genus is known for a high degree of phenotypic plasticity and variation in life history types (e.g., resident, migratory, anadromous; Dunham et al 2008).…”
mentioning
confidence: 99%